The role of the United Nations Convention on the Rights of Persons with Disabilities and the Human Rights Model (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The protection of the rights of persons with disabilities has undergone an extraordinary development in recent decades, culminating in the adoption of the United Nations convention on the rights of persons with disabilities. The latter has become the cornerstone of an ongoing legal and cultural revolution, based on adherence to the so-called human rights model. Moreover, the convention boosted a change in the global system of protection of human rights. Against this background, this contribution argues that some of the provisions of the convention have acquired the value of a source of general international law, thus providing a further interpretive tool for a affirming a higher standard of protection of disability rights.
Keywords: United Nations convention on the rights of persons with disabilities; human rights model; human rights law; disability law; general international law